Silver(I) And Gold(I) Mono-, Bis- And Tetra-N-Heterocyclic Carbene Complexes: Synthesis, Characterization, Antibacterial And Photophysical Studies - Haziz, Umie Fatihah Mohamad (2021)
This work describes the synthesis of symmetrical and non-symmetrical benzimidazolium salts as a precursor for the silver(I)-NHC complexes (where NHC = N-heterocyclic carbene). For the first series, seven n-butyl-n’- alkylbenzimidazolium bromide salts (where alkyl = methyl, ethyl, n-propyl, npentyl, n-hexyl, n-heptyl and n-benzyl), 1-7 were successfully synthesized. The second series, salts 8-10 were synthesized from n-alkylbenzimidazole (where nalkyl = ethyl, n-propyl and n-butyl) with 1,2-dibromoethane, while salts 11-13 were synthesized from n-benzylbenzimidazole with 1,n-dibromoalkane (where alkane = ethane, propane and butane). Meanwhile, through the reaction of 3-(2- bromoethyl)-1-butylbenzimidazole bromide, iii with n-alkylbenzimidazole (where n-alkyl = methyl, ethyl, n-propyl, n-pentyl, n-hexyl, n-heptyl and n-benzyl), seven unprecedented non-symmetry dibenzimidazolium bromide salts, 14-20 were successfully obtained in the third series. The last series, tetradentate benzimidazolium salts 21-28 were successfully synthesized through the reaction of 3-(2-bromoethyl)-1-alkylbenzimidazole bromide salts (where alkyl = ethyl, npropyl, n-butyl and n-benzyl), i-iv with either 1,4-butylbisbenzimidazole or 1,3- bis(methylbenzimidazole)benzene. Salts 1-28 were reacted with silver(I) oxide in appropriate molar ratio via in-situ deprotonation reaction to facilitate the formation of silver(I)-NHC complexes Ag1-Ag28, respectively.